Occupational stress among armed forces and police personnel: a review - Srivastava, Manushi; Singh, Gunjan; Kharwar, Poonam Singh; Jaiswal, Shweta (International Journal Of Community Medicine And Public Health, 2023)
In today’s world, stress is a word which is hard to avoid. If someone asks people about their stress and specifically how they know it exists- two general types were described. First, there are experiences of mental distress, - often accompanied by feelings of not being able to cope, that things are falling apart, that the person is not in control of themselves and their situation or is just a general case that without specific reasons that all is not well. Secondly, the physiological manifestations of less appetite, sleeplessness, sweating, ulcers and physical illness of various degrees. Different people have different views about it from various, sources. Occupational stress can be explained as the physiological and emotional responses that originate when personnels feel an imbalance between their work demands and their capability and response to meet these demands. Purpose of this paper is to provide a general review on “occupational stress among armed forces and police personnel of India” with the help of available literature. The home ministry commissioned conducted a study to look into the reasons for premature retirements of paramilitary forces. The findings of the study revealed that lack of sleep, manpower crunch, no leaves and lack of motivation were some of the reasons responsible for people quitting the jobs. However, to the best of my knowledge, no specific research study has been carried-out in India till date to assess the rate and reason of suicides among armed forces and even the home ministry’s official statement revealed that, in most of the cases of suicides, the reasons are more personnel than work related.